أثر السياسات التوزيعية على الأداء التسويقي للمنشآت الدوائية السورية - ناصر محمد جودت; حمود أحمد محمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تبين هذه الدراسة أن سياسات التوزيع لم تعد تقتصر على العمليات التي تساعد على توفير المنتج للمستهلك النهائي في الزمان والمكان المناسبين فحسب، بل إنه في ظل المنافسة الشديدة واتساع الأسواق وزيادة المتطلبات والاحتياجات فقد أصبح للتوزيع وظائف استراتيجية تتجاوز عملية إيصال المنتج إلى الزبون. وعليه فالمنظمات الدوائية يجب أن تتبنى الاتجاهات الحديثة في تحديد سياساتها التوزيعية بما يعزز من قدراتها التنافسية ويضمن لها البقاء والنمو في السوق، وخصوصاً أن الصناعة الدوائية صناعة تنافسية بالدرجة الأولى. ويتناول هذا البحث دراسة أهم النقاط المتعلقة بمفهوم التوزيع الدوائي وأهميته ووظائفه وطرقه, بالإضافة إلى تحديد أهم العوامل المؤثرة في اختيار قنوات التوزيع الدوائي، كما أنه يركز في جانبه العملي على واقع النشاط التوزيعي في المنشآت الدوائية السورية وأهم مواضع النقص والقصور فيها، ويخلص إلى مجموعة من النتائج الهامة التي تم التوصل إليها من خلال توزيع قوائم الاستبيان وأهمها عدم اتباع المعايير السليمة في انتقاء الموزعين, وافتقار هذه المنشآت إلى وجود كادر متخصص مهمته الإشراف المستمر على الموزعين وإجراء الدورات التدريبية لهم, إضافة"إلى بعض النتائج التي تم التوصل إليها من خلال المقابلات الشخصية مع المعنيين بتوزيع الدواء سواء في القطاع العام أو الخاص وعلى رأسها عدم وجود سعي جاد لدى قسم كبير من المنشآت الدوائية السورية إلى امتلاك شبكات توزيع خاصة بها تمكنها من التوزيع المباشر, ووجود بعض النواحي السلبية المتعلقة بالتوزيع المادي من نقل وتخزين وتبريد, ويقدم البحث مجموعة من المقترحات والتوصيات التي من شأنها أن تساهم في تطوير سياسات التوزيع المتبعة في منشآتنا الدوائية بما يحقق مستوى أفضل من الكفاءة والأداء التسويقي لهذه المنشآت. This study shows that distribution policies are no longer limited to the processes that help deliver products to the final consumer at the right place and time. With the existence of such highly competitive atmosphere, the expansion of markets and the increase in requirements and needs , distribution has gained strategic functions that go beyond the process of product delivering. Therefore, pharmacological institutions have to adopt the modern trends in limiting their distribution policies in such a way that enhances the competitive abilities, and ensures survival and growth in the market, especially that the pharmacological industry is, in the first place, a competitive industry . This research studies the most important points related to the pharmacological distribution concept: its importance, functions and methods, in addition to defining the most important factors that affect the selection of pharmacological distribution channels . It also focuses, in its practical part, on the reality of distribution activity in the Syrian pharmacological institutions and of their weakness and insufficiency. It, via conducting a questionnaire, uncovers a set of important facts: Distributors are chosen on a wrong basis that goes against required standards. These institutions lack any specialized staff that can constantly supervise the distributors and make them attend training courses. Moreover, personal interviews with parties concerned with drug distribution in both public and private sectors have shown that there is a lack of serious effort on the part of a great number of Syrian pharmacological institutions to have their own distribution networks. This helps make direct distribution possible . There are also some negative points related to material aspects of distribution such as transport, storage and cooling . This study , also , provides a set of suggestions and recommendations that contribute to the development of distribution policies adopted in our pharmacological institutions in order to achieve a better level of proficiency and marketing performance.